Axiomatique constitutionnelle et pratique politique : un décalage troublant - Arbour, J.-Maurice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The object of this paper is to consider the place which theory occupies within the framework of our parliamentary system. In particular, the purpose of this essay is to analyse the gap which exists between legal theories and facts. While a knowledge of the past is a prerequisite to interpreting the present and estimating the future, it will only be possible in this paper to give a brief review of basic historical data ; it is an essay in law, not in legal history. Students of constitutional law have long been only students of the cases in relation to federalism. Constitutional issues that trouble the conduct of our parliamentary system are not those with which constitutional lawyers are familiar. Issues surrounding the separation of powers are critical for the safeguard of civil liberties. It is time to consider what problems have been encountered and what plans for the future could be accepted or proposed for a better working of our parliamentary gouvernment.